Exploring the role of speaking in second language acquisition: Key challenges learners face and effective strategies applied - Sheenaz Dhia Raisha Windriya; Majid Wajdi; Rodolfo P. Dizon Jr; Md. Kamrul Hasan; Nadia Idri (Journal of Language and Pragmatics Studies, 2025)
This study explores the central role of speaking in second language acquisition (SLA), highlighting its importance in communication, intercultural interaction, and the development of communicative competence. The research aims to identify challenges learners face in developing oral proficiency and to evaluate pedagogical strategies that enhance speaking performance. Using a qualitative descriptive approach through document analysis, the study reviews applied linguistics and English as a Foreign Language (EFL) literature published between 2015 and 2024. Findings indicate that learners frequently encounter obstacles such as language anxiety, limited opportunities for authentic practice, inadequate exposure to real-life communication, and an overemphasis on reading and writing in educational contexts. These challenges restrict fluency, accuracy, and learners’ willingness to communicate. Nonetheless, several strategies have proven effective in improving speaking skills. These include task-based learning, communicative classroom activities, targeted pronunciation training, integration of digital tools, and anxiety-reducing techniques. Additionally, supportive learning environments and peer collaboration are shown to boost learners’ confidence and engagement. The study concludes that speaking instruction in SLA should adopt an integrated approach that combines linguistic, psychological, and sociocultural support. Through communicative and technology-enhanced strategies, educators can strengthen learners’ fluency, reduce speaking anxiety, and foster effective language acquisition.